Electricity Consumption and Export Performance: Evidence from Nepal - Paudel, Ramesh C.; Thapa-Parajuli, Resham; Alharthi, Majed (International Journal of Energy Economics and Policy, 2020)
This paper, noting positive marks due to regular supply of electricity and increased consumption of its, examines the role of electricity consumption in export performance of Nepal employing the Autoregressive distributed lag (ARDL) approach of cointegration for the period of 1975-2018. The results show that electricity does have a strong long-run positive relationship with the export performance of Nepal. Therefore, it can be suggested, based on the results, that increasing electricity consumption might increase the exports values. Also, there is a need for building infrastructure to support production activities, not just the means of transportation to reach our villages. Only those infrastructures focused on production activities will contribute to increasing the exports attracting more foreign direct investment in the country. Keywords: Energy, Electricity, Export performance, Nepal JEL Classifications: O13, L94, F13, O53 DOI: https://doi.org/10.32479/ijeep.10524